Origen y significado de las estructuras en Lévi-Strauss. Carmen María de Hernández - Hernández, Carmen María de (San José, C.R : EUCR, 1973)
Análisis de las estructuras según Claudio Levi-Strauss
Keywords: FILOSOFIA; SOCIEDAD; ESTRUCTURALISMO; LEVI-STRAUSS, CLAUDIO